Effect of ascorbic acid deficiency on the growth, gill filament lesions and behavior of pacu fry (Piaractus mesopotamicus Holmberg, 1887) - Martins, M. L. [UNESP] (My University, 1995)
The effect of ascorbic acid deficiency was determined in Piaractus mesopotamicus Holmberg, 1887, fish (pacu) under laboratory conditions. A total of 120 fish with an average body weight of 8.64 ± 1.62 g and measuring 6.15 ± 0.33 cm in length at the beginning of the experiment were fed diets containing 0, 50, 100 or 200 mg palmitate-coated ascorbic acid/kg dry ration for a period of 24 weeks with measurements every 4 weeks. The experiment was conducted in 20 fiber-cement aquaria of 81-liter capacity. Each aquarium was supplied with dechlorinated water at a flow rate of 1 l/min. Water temperature was measured daily and pH, dissolved oxygen, alkalinity and water conductivity were determined weekly. A fully randomized experimental design was utilized, with 5 replicates of each treatment and 6 fish per aquarium. Arcorbic acid-supplemented fish presented significantly increased growth when compared to unsupplemented fish. Furthermore, unsupplemented fish presented a higher incidence of hyperplasia, hypertrophy and dysplasia of the bone cartilage of gill filaments. The gill lamellae of unsupplemented fish had twisted cartilage and an inflammatory infiltrate at the ends. Anorexia and increased handling stress were also observed in fish fed the unsupplemented diet. The present study suggests that 50 mg ascorbic acid/kg dry ration is sufficient to improve development of pacu fingerlings but the optimum level under aquarium conditions, determined by regression analysis, is 139 mg ascorbic acid/kg dry ration.
Keywords: ascorbic acid deficiency; histopathology; pacu fingerlings; Piaractus mesopotamicus